ANALISA TINGKAT PELAYANAN JALAN PADA RUAS JALAN GAJAYANA KECAMATAN LOWOKWARU KOTA MALANG - Imarianto, Georgius; Pandulu, Galih Damar; Arifianto, Andi Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Gajayana street, Lowokwaru District, Malang City is a busy road, because along the Gajayana street there are many places of activity centers such as schools, colleges, shopping centers and offices. Therefore, to solve the traffic problems of the street Gajayana to investigate the road capacity and level of service, to predict traffic volume five years in future. In the implementation of data collection on the Gajayana street, with one km road length, the methods used are manual counters methods, the implementation of data collection was conducted over seven days. From the data analysis on the roads Gajayana street can be seen that the capacity of the Gajayana street of 2507.92 pcu/hour, while the volume of traffic on the Gajayana street amounted to 3089.35 pcu/hour. From the comparison between V/C or degree of saturation on the Gajayana street 1.23 and level of service on Gajayana street at the level of road service was at category F or the worst. Keyword : analysis, level of service, gajayana street